THE ROLE OF THE TEACHER IN IMPLEMENTING THE INCULCATION OF EDUCATIONAL VALUES. AL-QURAN AND HADITH-BASED CHARACTERS AT SMP PLUS DARUL ILMI MURNI, DELI SERDANG REGENCY - Abd. Mukti; Junaidi Arsyad; Achmad Bahtiar (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the teacher's role in implementing the inculcation of educational values. Al-Quran and Hadith-based characters at SMP Plus Darul Ilmi Murni, Deli Serdang Regency. The method in this research is descriptive qualitative. Data collection techniques using observation, interviews and documentation studies. Data analysis was carried out using interactive model data analysis techniques consisting of data collection, data testing, data reduction and drawing conclusions. The results of this study illustrate that the teacher plays a role in compiling and developing curriculum, syllabus, lesson plans, teaching materials, and methods by integrating with the Al-Quran and Hadith, as well as conveying advice and examples to students. Parents participate and support by educating, supervising, and setting an example in the family environment.